Delirium in the intensive care setting dependent on the Richmond Agitation and Sedation Scale (RASS): Inattention and visuo-spatial impairment as potential screening domains. Issue 2 (April 2020) - Boettger, Soenke; Meyer, Rafael; Richter, André; Rudiger, Alain; Schubert, Maria; Jenewein, Josef; Nuñez, David Garcia
Abstract: Objective: In the intensive care setting, delirium is a common occurrence; however, the impact of the level of alertness has never been evaluated. Therefore, this study aimed to assess the delirium characteristics in the drowsy, as well as the alert and calm patient. Method: In this prospective cohort study, 225 intensive care patients with Richmond Agitation and Sedation Scale (RASS) scores of −1 — drowsy and 0 — alert and calm were evaluated with the Delirium Rating Scale-Revised-1998 (DRS-R-98) and the Diagnostic and Statistical Manual 4th edition text revision (DSM-IV-TR)-determined diagnosis of delirium. Results: In total, 85 drowsy and 140 alert and calm patients were included. Crucial items for the correct identification of delirium were sleep–wake cycle disturbances, language abnormalities, thought process alterations, psychomotor retardation, disorientation, inattention, short- and long-term memory, as well as visuo-spatial impairment, and the temporal onset. Conversely, perceptual disturbances, delusions, affective lability, psychomotor agitation, or fluctuations were items, which identified delirium less correctly. Further, the severities of inattentiveness and visuo-spatial impairment were indicative of delirium in both alert- or calmness and drowsiness. Significance of results: The impairment in the cognitive domain, psychomotor retardation, and sleep–wake cycle disturbances correctly identified delirium irrespective of the level alertness. Further, inattentiveness and — to a lesser degree — visuo-spatial impairment could represent a specific marker for delirium in the intensive care setting meriting further evaluation.